PERATURAN DAERAH BERMASALAH - Luky Sandra Amalia (Masyarakat Indonesia, 2011)
Based on the higher constitution, local government has their own rights tomanage public interest in their local area. Therefore, local government needsto create local rules to breakdown the higher constitution but still remainlocal characteristics. Unfortunately, there are many local rules which arerecognized as contradiction with the higher constitutions, unable to containnational interest, unable to contain local social context, incompatible withpublic interest, and those are not aspirated by society. These local rules wererecommended to be revised or canceled. It popular as complicated local rules.Generally, the dominants of complicated local rules are about local taxes andretributions because district autonomy implementation in?uence local cost.The situation became more complicated because policy making process doesnot involve society, whereas mass participation in policy making process isvery important to do because people involvement could be an effective controlso the local government does not use local rules as a tool to discriminate orburden certain community. So, there are many problems of local rules whichare needed more attention to make it better